نشأة الخطاب الفلسفي الغربي الحديث وتحولاته (من التأسيس إلى التشظي) - سعيدة تليلي (جامعة الوادي - University of Eloued, 2025)
"تسعى هذه المذكرة إلى تتبع المسار التاريخي والفلسفي لنشوء وتطور وانهيار الخطاب الفلسفي الحداثي من خلال ثلاث مراحل مركزية: التأسيس، التبلور، ثم التصدع والتشظي. ينطلق الفصل الأول من لحظة انحسار العصر الوسيط حيث أدت التحولات الاجتماعية والاقتصادية خاصة صعود البرجوازية وتراجع هيمنة الكنيسة إلى أحداث قطيعة مع المنظومة الفكرية القديمة، مع عصر النهضة بدأت ملامح جديدة تظهر مثل الحركة الإنسانية التي أعادت الاعتبار للإنسان والإصلاح الديني الذي هز سلطة الكنيسة، بالإضافة إلى الثورة العلمية التي فتحت الباب أمام تصور جديد للكون والمعرفة منفصلاً عن التقليد الأرسطي. في الفصل الثاني ننتقل إلى مرحلة تشكل الخطاب الفلسفي الحداثي حيث أصبح العقل والمنهج أساساً لبناء المعرفة، ظهر ذلك أولاً في المشروع التجريبي مع فرانسيس بيكون ثم العقلانية الديكارتية ما أدى إلى انقسام واضح بين التجريبيين والعقلانيين حول مصدر المعرفة، جاء إيمانويل كانط لاحقاً ليحاول تجاوز هذا الانقسام عبر نقد العقل الخالص فاتحاً بذلك مرحلة جديدة من التفكير الفلسفي، كما عرف هذا العصر صعود فكر التنوير الذي حمل طموحات كبرى في تحرير الإنسان، إلى جانب تشكل الفلسفة المثالية مع هيجل التي حاولت بناء نسق عقلاني شامل للواقع. لكن هذه الطموحات لم تدم طويلاً، في الفصل الثالث نرصد بداية تصدع الخطاب الحداثي حيث وجه فلاسفة مثل ماركس ونيتشه وفرويد انتقادات حادة للمفاهيم الحداثية مثل العقل والذات والوعي، معتبرين أن هذه المفاهيم تخفي سلطات عميقة أو وهماً معرفياً، ثم جاءت محاولات لترميم هذا المشروع مع هوسرل وكاسيرر لكنها لم تمنع ظهور خطاب ما بعد الحداثة الذي أعلن القطيعة مع كل مركزية عقلانية، ودعا إلى تفكيك الثنائيات الكبرى وإعادة التفكير في المعرفة والمعنى والسلطة. " This study traces the historical and philosophical trajectory of the emergence, development, and decline of modern philosophical discourse through three central phases: foundation, crystallization, and subsequent fragmentation. The first chapter begins with the waning of the medieval era, where socioeconomic transformations - particularly the rise of the bourgeoisie and the decline of ecclesiastical dominance - precipitated a rupture with traditional intellectual systems. The Renaissance witnessed emerging paradigms: the humanist movement restoring human dignity, religious reformation challenging Church authority, and scientific revolution establishing new cosmological and epistemological frameworks independent of Aristotelian tradition. The second chapter examines the formation of modern philosophical discourse, where reason and methodology became foundational for knowledge construction. This manifested initially in Bacon's empirical project and Cartesian rationalism, creating a clear epistemological divide between empiricists and rationalists. Kant later attempted to transcend this dichotomy through his critique of pure reason, inaugurating a new philosophical era. This period also saw Enlightenment thought advocating human emancipation and Hegel's idealist system constructing a comprehensive rational framework for reality. However, these aspirations proved transient. The third chapter documents modernism's disintegration through Marx, Nietzsche, and Freud's radical critiques of modern concepts like reason, subjectivity, and consciousness, revealing their hidden power structures or epistemic illusions. Though Husserl and Cassirer attempted restoration, postmodern discourse ultimately emerged, rejecting all rationalist centrisms and advocating deconstruction of fundamental binaries while rethinking knowledge, meaning, and power relations. Collectively, this study provides a comprehensive analysis of modernity's trajectory from inception to fragmentation, illuminating the philosophical transformations that shaped contemporary thought
مذكرة ماستر قسم الفلسفة تخصص فلسفة عامة.
Keywords: ما بعد الحداثة; المنهج النقدي; المنهج التجريبي; المنهج العقلاني; عصر النهضة; العصور الوسطى; الفلسفة الحديثة; Modern Philosophy; Middle Ages; Renaissance; Rational Method; Experimental Method; Critical Method; Postmodernism